Analysis of Student Needs in Implementing Counseling Services at SMP Negeri 94 Central Maluku - Emma Rumahlewang; Sawal Mahaly; Jeanete O. Papilaya (Peneliti.net, 2023)
Students at school are individuals who will definitely face various problems, but the complexity and types of problems experienced by each individual can vary. Problems that are generally experienced by students can be related to personal, social, learning, and career problems. In helping students overcome these problems, guidance and counseling teachers play an important role. By understanding and identifying specific problems, teachers can design appropriate guidance and counseling programs to help students deal with their personal, social, learning, and career problems. The purpose of this research is to help teachers, especially guidance and counseling teachers to carry out guidance and counseling services according to the needs of students. This type of research is a descriptive study with a sample of 64 students at SMP Negeri 94 Central Maluku. The method of determining the sample using saturated sampling.Based on the results of data processing, it can be concluded that the most dominant problem occurs in class IX. In this class, learning problems are the most dominant problem with a score of 117 (32.32%). This shows that class IX students at SMP Negeri 94 Central Maluku face difficulties in terms of information on graduation requirements and how to increase their concentration in studying. Therefore, it is necessary to give special attention and further efforts to assist students in overcoming these learning problemss.